Stockley's drug interactions. - Baxter, Karen, ....- (London : Pharmaceutical Press, 2007)
Stockley's Drug Interactions, edited by Karen Baxter, remains the world's most comprehensive and authoritative reference book on drug interactions. Contains detailed yet concise monographs Covers interactions between therapeutic drugs, proprietary medicines, herbal medicines, foods, drinks, pesticides and drugs of abuse Based on published sources and fully referenced Provides comprehensive details of the clinical evidence for the interactions under discussion, an assessment of their clinical importance and gives clear guidance on how to manage the interaction in practice Covers over 17,000 indexed interaction pairs Contains over 3,100 monographs
Keywords: Geneesmiddelen